An anthropologist in Japan : glimpses of life in the field - Hendry, Joy (ASA research methods in social anthropology (Routledge (Firm)), 1999)
In this highly personal account Joy Hendry relates her experiences of fieldwork in a Japanese town and reveals a fascinating cross-section of Japanese life. She sets out on a study of politeness but a variety of unpredictable events including a volcanic eruption, a suicide and her son's involvement with the family of a poweful local gangster, begin to alter the direction of her research. The book demonstrates the role of chance in the acquisition of anthropological knowledge and demonstrates how moments of insight can be embedded in everyday activity. An Anthropologist in Japan illuminates the education system, religious beliefs, politics, the family and the neighbourhood in modern Japan.